Między ratio a emotum. Polsko-rosyjskie postrzeganie wzajemne w perspektywie binarnej - Nakoneczny, Tomasz (Studia Rossica Posnaniensia, 2021)
A characteristic feature of Polish-Russian mutual perception is binarity, manifesting itself in various discursive spaces, from colloquial stereotypes, through popular literature, to sophisticated forms of meta-historical discourse. Asian-Europeanness, Latin-Byzantism/Orthodoxy, collectivism-individualism, and authenticity-falsehood, are just some of the oppositions that organise the social imagination of Poles and Russians in the sphere of their mutual assessments and opinions. The article draws attention to the partial manifestations of such oppositions (literary discourse, postcolonial studies, etc.) in order to show their hidden, dialectical dimension. To achieve this goal, the author refers to the category of ratio and emotum, which refers to a specific current of the European philosophical tradition. Both of these binary categories are the foundation for creating an image of the Other. They also fit into self-defining strategies important for understanding Polish and Russian identity.